Applicability of Lean Manufacturing on Operational Performance - A Case Study in the Apparel Industry in Sri Lanka - Silva, S. K. P. N. (Prabandhan: Indian Journal of Management, 2011)
Lean Manufacturing is a manufacturing philosophy which was originated and developed in "Toyota Motor Company" Japan. It tries to identify wastes in the processes and eliminate it. Thus, it leads to improvement in productivity and quality in organizations, leading to a competitive advantage over others. Different industries have applied Lean concepts in order to improve their bottom-line. This paper tries to identify the applicability of Lean to a new sector - the "Sri Lankan apparel industry". As the initial stage, a literature review was carried out to study about Lean Manufacturing. The next step was to explore how Lean Manufacturing can be effectively applied in the Sri Lankan apparel sector. The purpose of this paper is to investigate the applicability of Lean Manufacturing concepts in apparel manufacturing organizations in Sri Lanka, using a case-based approach. The research was administered with one of the leading apparel manufacturers in Sri Lanka, using personal interviews, secondary data and observations. Existing batch production line was analyzed and various improvement proposals were implemented based on Lean Manufacturing theories. The findings revealed that Lean Manufacturing can be applied to mass production apparel production line, in order to derive positive results such as reducing wastes in inventory and defects. Further, Lean has helped the managers of the case company to visualize the different types of wastes generated in the organization and future possibilities of eliminating or reducing them. The findings can be extended to similar apparel organizations in the future.